TECHNOLOGIES IN THE PREPARATION OF TEACHERS FOR THE USE OF A DIFFERENTIATED APPROACH IN PHYSICAL EDUCATION - Boltabayev Mirvokhid Mirzabdullayevich (International Scientific and Current Research Conferences, 2024)
The article explores modern methods and technologies used in the process of teacher training for the effective use of a differentiated approach in the field of physical education. The author examines the essence of the differentiated approach in the context of physical education and assesses its importance for different groups of students. The article also analyzes in detail innovative educational technologies, including virtual simulators, online courses and simulations, which can effectively support teachers in individualizing physical education training. As a result of the study, recommendations are offered on the use of modern technologies to improve the quality of education and ensure the successful implementation of a differentiated approach in physical education.